1998
DOI: 10.1111/j.1532-5415.1998.tb03805.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Phenotypes, Dementia and Mortality in a Prospective Population Sample

Abstract: In a population aged 75 to 85 years, the presence of an apoE e4 allele is associated with impaired cognitive function, clinical dementia, AD, and excess 5-year mortality resulting from dementia and all causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 23 publications
8
63
4
Order By: Relevance
“…Third, we found that, among noncarriers of APOE ε4, borderline diabetes led to a higher risk of Alzheimer's disease, which is in accordance with a recent report that the association between diabetes and incident Alzheimer's disease was present only in APOE ε4 -negative individuals (41). One explanation is that the strength of association between APOE ε4 and Alzheimer's disease decreases with increasing age (42,43), and APOE ε4 is also associated with excess mortality (44). Thus, it is likely that those with ε4 allele have either died or been diagnosed with dementia in this elderly population, and the observed borderline diabetes-Alzheimer's disease association among APOE ε4 allele noncarriers might be due to selective survival (45).…”
Section: Discussionsupporting
confidence: 91%
“…Third, we found that, among noncarriers of APOE ε4, borderline diabetes led to a higher risk of Alzheimer's disease, which is in accordance with a recent report that the association between diabetes and incident Alzheimer's disease was present only in APOE ε4 -negative individuals (41). One explanation is that the strength of association between APOE ε4 and Alzheimer's disease decreases with increasing age (42,43), and APOE ε4 is also associated with excess mortality (44). Thus, it is likely that those with ε4 allele have either died or been diagnosed with dementia in this elderly population, and the observed borderline diabetes-Alzheimer's disease association among APOE ε4 allele noncarriers might be due to selective survival (45).…”
Section: Discussionsupporting
confidence: 91%
“…Dementia at baseline was diagnosed as described previously. 11 The individuals were classified as healthy elderly if their subjective or objective (according to the physician) health was good or moderate, if they did not suffer from any significant clinical disease, and if they had a normal reported exercise tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…ApoE phenotype was determined as described previously. 11 Dehydroepiandrosterone (DHEA) was measured with a commercial kit (Coat-A-Count DHEA-soy, Diagnostics Products). 12 The census status (100%) was determined annually until December 1998.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a population-based prospective study of individuals over age 75, revealed a relative risk for developing AD of 3.24 (95% CI, 1.67-6.25) in those possessing ApoE4. 52 However, the sensitivity (approximately 50%) and specificity (approximately 75%) for the presence of the ApoE4 genotype in diagnosing AD is insufficiently high to guide diagnosis or accurately quantify genetic risk. 52,53 …”
Section: Genetics Of Dementiamentioning
confidence: 99%